COVID-19 booster vaccination uptake and infection breakthrough amongst health care workers in Wales: A national prospective cohort study. Issue 7 (10th February 2023) - Bedston, Stuart; Lowthian, Emily; Jarvis, Christopher I.; Akbari, Ashley; Beggs, Jillian; Bradley, Declan; de Lusignan, Simon; Griffiths, Rowena; Herbert, Laura; Hobbs, Richard; Kerr, Steven; Lyons, Jane; et al.
Highlights: Overall, booster uptake was at 91% by 29th February 2022. Uptake lower in more deprived areas and the Black ethnic group. Booster uptake comparable to first dose under primary schedule. Booster infection breakthrough most likely for those living with children. Booster breakthrough comparable to second dose under primary schedule. Abstract: Background: From September 2021, Health Care Workers (HCWs) in Wales began receiving a COVID-19 booster vaccination. This is the first dose beyond the primary vaccination schedule. Given the emergence of new variants, vaccine waning vaccine, and increasing vaccination hesitancy, there is a need to understand booster vaccine uptake and subsequent breakthrough in this high-risk population. Methods: We conducted a prospective, national-scale, observational cohort study of HCWs in Wales using anonymised, linked data from the SAIL Databank. We analysed uptake of COVID-19 booster vaccinations from September 2021 to February 2022, with comparisons against uptake of the initial primary vaccination schedule. We also analysed booster breakthrough, in the form of PCR-confirmed SARS-Cov-2 infection, comparing to the second primary dose. Cox proportional hazard models were used to estimate associations for vaccination uptake and breakthrough regarding staff roles, socio-demographics, household composition, and other factors. Results: We derived a cohort of 73, 030 HCWs living in Wales (78% female, 60% 18–49 years old). Uptake was quickest amongst HCWs aged 60 + years old (aHR 2.54, 95%CI 2.45–2.63), compared with those aged 18–29. Asian HCWs had quicker uptake (aHR 1.18, 95%CI 1.14–1.22), whilst Black HCWs had slower uptake (aHR 0.67, 95%CI 0.61–0.74), compared to white HCWs. HCWs residing in the least deprived areas were slightly quicker to have received a booster dose (aHR 1.12, 95%CI 1.09–1.16), compared with those in the most deprived areas. Strongest associations with breakthrough infections were found for those living with children (aHR 1.52, 95%CI 1.41–1.63), compared to two-adult only households. HCWs aged 60 + years old were less likely to get breakthrough infections, compared to those aged 18–29 (aHR 0.42, 95%CI 0.38–0.47). Conclusion: Vaccination uptake was consistently lower among black HCWs, as well as those from deprived areas. Whilst breakthrough infections were highest in households with children.